Effects of Soil and Water Salinity on Ph, Ec and the Selected Ion Contents in Different Crops Grown in Nonsaline and Salinity Affected Areas of Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Abstract Not AvailableAsiat. Soc. Bangladesh, Sci. 43(1): 129-133, June 2017